Assessment of the reliability of a novel self-sampling device for performing cervical sampling in Malaysia - Abd Latiff, Latiffah; Abdul Rahman, Sabariah; Wong, Yong Wee; Dashti, Sareh; Andi Asri, Andi Anggeriana; Unit, Nor Hafeeza; Foo, Shirliey Siah Li; Esfehani, Ali Jafarzadeh; Ahmad, Salwana (Asian Pacific Education Press Ltd., 2015)
Background: The participation of women in cervical cancer screening in Malaysia is low. Self-sampling might be able to overcome this problem. The aim of this study was to assess the reliability of self-sampling for cervical smear in our country.